2015
DOI: 10.1159/000438482
|View full text |Cite
|
Sign up to set email alerts
|

Measuring End-Tidal Carbon Monoxide of Jaundiced Neonates in the Birth Hospital to Identify Those with Hemolysis

Abstract: Background: End-tidal breath carbon monoxide (ETCOc) levels correlate with catabolism of heme, but until recently, this measurement was not readily available for application to neonatology practice. Objectives: We performed a prospective, multihospital, test-of-concept study where ETCOc was measured during the birth hospitalization of neonates with a total bilirubin (TB) value >75th percentile on the Bhutani bilirubin nomogram. This was done to test the feasibility and ease of use of this new device. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The kinetic cause of this variety of anemia is thought to be hemolytic, on the basis of hyperbilirubinemia and reticulocytosis. Our findings of an elevated end-tidal CO and absent haptoglobin are supportive of a hemolytic pathogenesis [24,25].…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…The kinetic cause of this variety of anemia is thought to be hemolytic, on the basis of hyperbilirubinemia and reticulocytosis. Our findings of an elevated end-tidal CO and absent haptoglobin are supportive of a hemolytic pathogenesis [24,25].…”
Section: Discussion/conclusionsupporting
confidence: 76%
“…Lozar-Krivec and colleagues 75 found that HbCO was higher in newborns with hemolysis than in those without hemolysis. The authors of several studies [76][77][78] suggest that measurement of exhaled CO is a feasible approach to assessing hemolysis in jaundiced neonates. Exhaled CO might also be useful to monitor hemolysis in children with sickle cell disease.…”
Section: Heme Oxygenasementioning
confidence: 99%
“…FDA-approved point-of-care noninvasive monitors can quantify the end-tidal CO of neonates. Our recent work, and that of others, has shown that measuring ET-COc during newborn hospitalization can identify hemolysis [19][20][21]. In our new management program, we will obtain an ETCOc on all neonates who meet the phototherapy initiation criteria.…”
Section: Etcoc Measurement For Those Receiving Phototherapy To Determmentioning
confidence: 99%